Reforming Journalism Education on a Tertiary Level in Afghanistan: Recommendations for a Dual Education Model (Global Media Journal - German Edition, 2021)
The importance of journalism’s role in society is beyond debate. Particularly in so-called fragile states, the social responsibility of media and journalism cannot be denied. Journalism education must account for the high level of skills required by journalists, and the ‘mediation’ function of journalists in fragile states should be conceptualised. Responding to dynamic developments in the Afghan media landscape and the resulting need for high-quality journalism education, this article proposes a reform model for journalism education on a tertiary level in Afghanistan. Based on research as well as a needs and feasibility assessment following the participatory action research (PAR) approach, target models and an implementation plan for educational reform were developed. This provides a potential blueprint for reforms in journalism education in fragile states, which considers social and cultural values and interests in the local context while drawing on the perspective of the outsider. This article presents the results of a project entitled “Professionalisation of Journalism Education on a Tertiary Level in Afghanistan”, which resulted in a manual.
Keywords: communication studies; journalism; journalism education; development communication; Afghanistan